Aptitud climática de un destino turístico semiárido : Primera aproximación sobre un caso argentino - Tanana, Ariadna Belén (2022)
El abordaje de la relación clima-turismo se ha expandido a través de la Climatología del Turismo, aunque las experiencias en destinos del hemisferio sur son escasas. Este artículo evalúa el confort bioclimático y climático-turístico de Mendoza, destino internacional de clima semiárido representativo de la región Cuyo. Se utilizó un enfoque cuantitativo basado en índices directos: bioclimáticos (complejo termo-higrométrico, complejo temo-anemométrico y temperatura equivalente) y climático-turísticos (Tourism Climate Index y Holiday Climate Index Urban). Para ello, se emplearon los datos medios mensuales de las últimas tres décadas disponibles (1981-2010). Conforme con los resultados, el verano es un momento crítico en términos del confort térmico. Sin embargo, según los índices climático-turísticos el destino es apto durante todo el año, aunque se contraponen con respecto al momento calificado como ideal para el turismo, poniendo en discusión su aplicabilidad en destinos de clima semiárido.
The approach to the climate-tourism relationship has expanded through the discipline of Tourism Climatology, although experiences in Southern hemisphere destinations are scarce. This article evaluates the bioclimatic and tourism climate comfort of Mendoza, an international destination with a semi-arid climate representative of the Cuyo region. A quantitative approach based on direct indices was used: bioclimatic (thermo-hygrometric complex, thermo-anemometric complex and equivalent temperature) and tourism climate (Tourism Climate Index and Holiday Climate Index: Urban). For this, the monthly mean data of the last three available decades (1981-2010) were used. According to the results, summer is a critical time in terms of thermal comfort. However, according to tourism climate indices, the destination is suitable throughout the year, although the indices disagree as to the ideal time for tourism, making their applicability to destinations with a semi-arid climate questionable.
Keywords: Confort; Facetas del clima; Climatología del turismo; Mendoza; Comfort; Climate Aspects; Tourism Climatology; Mendoza